Implementation, benefits, and challenges of the community development program of a Non-Government Organization in Negros Occidental - Alcorin, Ana T.; Verdeprado, Richelle H. (Technium Social Sciences Journal, 2022)
The study used descriptive and comparative research approaches to assess the extent of implementation of the community development program of a non-government organization (NGO) in Negros Occidental in the areas of education, health and social care, livelihood, and environment. Using stratified random sampling, 227 beneficiaries from the community and 12 implementers participated in the study. The data were gathered using the researcher-made instrument subjected to validity and reliability testing. Mean, standard deviation, and Mann Whitey U-test were used to analyze the data. The findings of the study revealed that the community development program was implemented to a high extent when taken as a whole and when grouped according to the designation of assessors in the areas of education, health and social care, livelihood, and moderate in the environment. There is a significant difference in the extent of implementation of the community development program in the areas of education and livelihood when the assessors are grouped according to the designation. Moreover, there is no significant difference in the extent of implementation of the community development program in the areas of health and social care and the environment when the assessors are grouped according to the designation. The study also identified several benefits, challenges, and recommendations. The results of the study led to enhanced community development implementation strategies to be presented to the BOM and beneficiaries.